Corporate social responsibility and corporate governance : concepts, perspectives and emerging trends in Ibero-America - Gómez, Lina M.; Crowther, David; Vargas, Lucely (Developments in corporate governance and responsibility ;, 2017)
This edited book focuses on how CSR and Corporate Governance in Ibero-America have been employed, analyzed, and examined in different sectors and scenarios. It takes a trans-regional approach unlike most research which has been focused on studying specific initiatives or experiences in a particular country.